2013
DOI: 10.21553/rev-jec.43
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach and Tool in Verifying Asynchronous Circuits

Abstract: Abstract-Research in asynchronous circuit approach has been carried out recently when asynchronous circuits are presented more widely in electronic systems. As they are more important in human life, their correctness should be considered carefully. Although there are some EDA tools for design and synthesis of asynchronous circuits, they are lack of methods for verifying the correctness of the produced circuits. In this work, we are about to propose a verification method and apply it in making a new version of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In [5], a combination of Petri Net and Data Flow Graph (PN-DFG) [7], which is used as the immediate-level language in representing asynchronous circuits, have been transformed into NuSMV, a very famous open-source symbolic model checking tool. The experimentation results have shown that the NuSMV models of the circuits can be verified easily [6].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In [5], a combination of Petri Net and Data Flow Graph (PN-DFG) [7], which is used as the immediate-level language in representing asynchronous circuits, have been transformed into NuSMV, a very famous open-source symbolic model checking tool. The experimentation results have shown that the NuSMV models of the circuits can be verified easily [6].…”
Section: Introductionmentioning
confidence: 93%
“…Research in representing Petri Nets in verification tools have been carried out recently [3] [4] [5] [6]. In [5], a combination of Petri Net and Data Flow Graph (PN-DFG) [7], which is used as the immediate-level language in representing asynchronous circuits, have been transformed into NuSMV, a very famous open-source symbolic model checking tool.…”
Section: Introductionmentioning
confidence: 99%